2019
DOI: 10.2174/1567202616666190131155834
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy Potentiated Hippocampal Cell Death Induced by Endoplasmic Reticulum Stress and its Activation by Trehalose Failed to be Neuroprotective

Abstract: Introduction: Endoplasmic reticulum (ER) stress induced the mobilization of two protein breakdown routes, the proteasomal- and autophagy-associated degradation. During ERassociated degradation, unfolded ER proteins are translocated to the cytosol where they are cleaved by the proteasome. When the accumulation of misfolded or unfolded proteins excels the ER capacity, autophagy can be activated in order to undertake the degradative machinery and to attenuate the ER stress. Autophagy is a mechanism by which macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Our data indicated that inhibition of autophagy eliminates the protective effects of PNS against ER stress response and associated cell death ( Figure 5 ), which is consistent with the report that under ER stress conditions, autophagy can be activated in order to undertake the degradative machinery to attenuate the ER stress. Inhibition of autophagy by trehalose exacerbates cell damage, and failed to exert neuroprotective function ( Halbe and Rami, 2019 ). Interestingly, we also found that PNS down-regulates the expressions of CHOP and Caspase-12, suggesting that CHOP-mediated ER stress apoptosis pathway may be involved in PNS protection against cardiac myocytes cell apoptosis, which is consistent with the previous report that saponins of Panax notoginseng suppressed the palmitate-induced ROS generation, and the ER stress-associated eIF2α/ATF4/CHOP and Caspase-12 pathways in RGC-5 cells ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicated that inhibition of autophagy eliminates the protective effects of PNS against ER stress response and associated cell death ( Figure 5 ), which is consistent with the report that under ER stress conditions, autophagy can be activated in order to undertake the degradative machinery to attenuate the ER stress. Inhibition of autophagy by trehalose exacerbates cell damage, and failed to exert neuroprotective function ( Halbe and Rami, 2019 ). Interestingly, we also found that PNS down-regulates the expressions of CHOP and Caspase-12, suggesting that CHOP-mediated ER stress apoptosis pathway may be involved in PNS protection against cardiac myocytes cell apoptosis, which is consistent with the previous report that saponins of Panax notoginseng suppressed the palmitate-induced ROS generation, and the ER stress-associated eIF2α/ATF4/CHOP and Caspase-12 pathways in RGC-5 cells ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%